Aktywa niematerialne jako źródło tworzenia wartości rynkowej przedsiębiorstwa - Michalczuk, Grażyna (Intangible Assets as a Source for Creating Company Market Value, 2007)
The market value of the company cannot be perceived solely from the angle of material resources I in the current market situation. The value of the company is determined to a large extent by intangible I assets, i.e. the employees' knowledge and skills, the culture of an organization, the information I technology resources, the list of regular customers and the like. All these components have common I features, they increase economic effectiveness. The achievements of modern organizations should be assessed from the angle of intangible assets. To achieve success, not only should the company have intangible assets difficult to copy, but also it should have the ability to use them in a practical way to a greater extent as well as have the ability of I sustained raising and accumulating such assets. It requires then a new structure of financial management in modern corporations, based not only on the analysis of traditional resources, but also on broadening the analysis to these resources which do not comply with the definition of assets according to the conservative accounting standards and cannot be presented in a currently prepared financial statement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 249-259